Hawaalah dalam Fiqih Muamalah: Dasar Hukum dan Prinsip Syariah - Resya Eka Putri; Chadiza Azzahra Lubis; Alexa Ayu Dewanda; Hanestesia Zahara; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Hawalah is the concept of debt transfer in Islamic law which is increasingly relevant in the digital era through the application of technology in the financial sector, such as fintech platforms. This research aims to explore the understanding of hawalah, including its sharia principles, as well as its benefits and risks in the context of modern finance. This research uses a qualitative descriptive method through literature studies that examine classical Islamic legal texts as well as books and journals related to sharia economic law. The research results show that hawalah allows debt transfer with the principle of being free from usury and gharar, and has pillars that must be fulfilled by the three parties involved: muhil, muhal, and muhal alaih.